Interfacial engineering of nanostructured photoanode in fiber dye‐sensitized solar cells for self‐charging power systems. Issue 3 (10th January 2022) - Song, Weixing; Bie, Zhe; Yan, Wei; Zhu, Junbo; Ma, Weiting
Abstract: Solar cells offer an environmentally sustainable and convenient option for power source of next‐generation wearable electronics. Due to the advantages of low cost, easy fabrication and deformation, fiber dye‐sensitized solar cells (FDSSCs) are required to be suitable for the available wearable electronics. Herein, through introduced nanopillar arrays over the Ti wire and atomic layer deposition of conformal TiO2 layer to make the photoanode, the energy conversion efficiency of the FDSSCs is improved by 45%. The FDSSCs are combined with planar microsupercapacitor (MSC) clusters to make self‐charging power system on a polymer sheet. The interdigital finger electrodes of MSC were obtained in a single‐step method by laser‐inducing on a polyimide film, and two series can be charged up to 1.8 V in 30 s by the FDSSCs under solar irradiation. This power sheet can be attached to various surfaces such as skin, cloths, and electronic devices for practical applications. Abstract : Fiber dye‐sensitized solar cells with interfacial engineering of photoanode, fabricated by introducing nanopillar arrays and a thin and conformal TiO2 layer over a Ti wire, offer significantly improved power conversion efficiency. Furthermore, micro‐supercapacitors based on laser‐induced graphene are made and combined with these fiber dye‐sensitized solar cells to form a thin‐sheet‐based self‐charging power system.